2018
DOI: 10.1111/jvp.12698
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic evaluation of marbofloxacin after intravenous administration at different ages in llama crias, and pharmacokinetic/pharmacodynamic analysis by Monte Carlo simulation

Abstract: In llama crias (tekes), Escherichia coli and Staphylococcus aureus are major pathogens, and marbofloxacin could be a suitable choice. The objectives of this study were (a) to evaluate the serum pharmacokinetics of marbofloxacin (5 mg/kg) after intravenous administration in tekes and simulate a multidose regimen; (b) to emulate pharmacokinetic profiles after single dose and steady-state conditions by Monte Carlo simulation (c) to determine the MIC of regional strains of Escherichia coli and Staphylococcus aureu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…In addition, they recommend administering balanced isotonic crystalloid fluids IV or performing a plasma transfusion. Rubio-Langre et al [ 80 ] showed that marbofloxacin is effective against E. coli infections in llama crias between 3 and 80 days of age at a dose of 5 mg/kg IV.…”
Section: Disease Caused By Escherichia Colimentioning
confidence: 99%
“…In addition, they recommend administering balanced isotonic crystalloid fluids IV or performing a plasma transfusion. Rubio-Langre et al [ 80 ] showed that marbofloxacin is effective against E. coli infections in llama crias between 3 and 80 days of age at a dose of 5 mg/kg IV.…”
Section: Disease Caused By Escherichia Colimentioning
confidence: 99%
“…Considering this, MC simulation could be a most useful approach in identification of ALB concentrations significance for inter‐individual MPA pharmacokinetic variability. 25 , 26 , 27 …”
Section: Introductionmentioning
confidence: 99%
“…Considering this, MC simulation could be a most useful approach in identification of ALB concentrations significance for inter-individual MPA pharmacokinetic variability. [25][26][27] The aim was the identification of mathematical correlation and association between both, total and unbound MPA concentration in relation to ALB, BM, age and eGFR in stable kidney transplant recipients. Furthermore, investigation was conducted with the aim to clarify the role of C SAL MPA in adverse effects profile.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial effect of fluoroquinolones is concentration‐dependent, and peak plasma concentration ( C max )/minimum inhibitory concentration (MIC) and area under the concentration–time curve (AUC 0–24 )/MIC ratios are used to evaluate their efficiencies. For maximum efficacy and minimal resistance in marbofloxacin treatment, the C max /MIC ratio is expected to be ≥10 for bacteria and AUC 0–24 /MIC ratio is expected to be ≥125 for gram‐negative bacteria and ≥60 for gram‐positive bacteria such as S. aureus (Lees, Concordet, Aliabadi, & Toutain, 2006; McKellar, Sanchez Bruni, & Jones, 2004; Rubio‐Langre et al, 2018; Toutain & Lees, 2004). In order to determine AUC 0–24 /MIC and C max /MIC, the pharmacokinetics (PKs) and pharmacodynamics (PDs) of marbofloxacin and the target species need to be specified.…”
Section: Introductionmentioning
confidence: 99%